Molecular changes in the equine follicle in relation to variations in antral follicle count and anti‐Müllerian hormone concentrations. (6th November 2015) - Claes, A.; Ball, B. A.; Troedsson, M. H. T.; Curry, T. E.; Squires, E. L.; Scoggin, K. E.
Summary: Reasons for performing study: The wide variation in circulating anti‐Müllerian hormone (AMH) concentrations between mares is attributed to differences in antral follicle count (AFC) which may reflect follicular function. There are few data regarding variations in AFC and associated regulatory factors for AMH in the equine follicle during follicular development. Objectives: To examine molecular and hormonal differences in the equine follicle in relation to variations in AFC and circulating AMH concentrations during follicular development and to identify genes co‐expressed with AMH in the equine follicle. Study design: Observational study. Methods: Plasma AMH concentrations and AFC were determined in 30 cyclic mares. Granulosa cells, theca cells and follicular fluid were recovered from growing (n = 17) or dominant follicles (n = 13). The expression of several genes, known to be involved in folliculogenesis and steroidogenesis, was examined using real‐time reverse transcriptase polymerase chain reaction and immunohistochemistry. Intrafollicular oestradiol and AMH concentrations were determined by immunoassay. Results: Within growing follicles, the expression of AMH, AMHR2, ESR2 and INHA in granulosa cells was positively correlated with AFC and plasma AMH concentrations. In addition, the expression of ESR1 and FSHR was positively associated with plasma AMH concentrations. No significant associations were detected in dominant follicles. Furthermore, there was no association between AMH or oestradiol concentrations in follicular fluid and variations in AFC. Finally, the expression of AMH and genes co‐expressed with AMH ( AMHR2, ESR2 and FSHR ) in granulosa cells as well as intrafollicular AMH concentrations decreased during follicular development while intrafollicular oestradiol concentrations increased and were inversely related to intrafollicular AMH concentrations. Conclusions: This study indicates that variations in AFC and circulating AMH concentrations are associated with molecular changes in the growing equine follicle.